Roux-en-O Gastric Bypass. Treatment of a Severe Complication - Velasco Hernandez, Norberto Daniel; Battista, Santiago B. De; Rivaletto, Lucas A.; Oro, Carolina Gómez (International Journal of Innovative Research in Medical Science, 2022)
Roux-O reconstruction in Y-bypass surgery is a rare and potentially devastating complication that can often be misdiagnosed. This occurs when the biliopancreatic loop anastomoses to the gastric pouch with the consequent evolution of the patient with intestinal obstruction, abdominal pain, nausea and/or bilious vomiting. We described A 27-year-old male patient who underwent surgery for morbid obesity with this complication. In conclusion, it should be considered that this less mentioned complication should be treated preventively, and in established cases, a Y-bypass reconstruction is the most appropriate solution.